Early modern privacy : sources and approaches - Green, Michael, 1980-; Nørgaard, Lars Cyril; Bruun, Mette Birkedal (Intersections (Boston, Mass.) ;, 2022)
"Privacy is often viewed as a modern phenomenon. Early Modern Privacy: Sources and Approaches challenges this view. This collection examines instances, experiences, and spaces of early modern privacy, and opens new avenues to understanding the structures and dynamics that shape early modern societies. Scholars of architectural history, art history, church history, economic history, gender history, history of law, history of literature, history of medicine, history of science, and social history detail how privacy and the private manifest within a wide array of sources, discourses, practices, and spatial programmes. In doing so, they tackle the methodological challenges of early modern privacy, in all its rich, historical specificity. Contributors include Ivana Bičak, Mette Birkedal Bruun, Maarten Delbeke, Willem Frijhoff, Michael Green, Mia Korpiola, Mathieu Laflamme, Natacha Klein Käfer, Hang Lin, Walter S. Melion, Hélène Merlin-Kajman, Lars Cyril Nørgaard, Anne Régent-Susini, Marian Rothstein, Thomas Max Safley, Valeria Viola, Lee Palmer Wandel, and Heide Wunder"--